Low Macrolide and Fluoroquinolone Susceptibility in Non-pathogenic Neisseriae in the General Belgian Population and STI Clinic Attendees. (March 2022) - Van Dijck, C.; Laumen, J.; Abdellati, S.; De Baetselier, I.; Martiny, D.; Kenyon, C.
Abstract : Purpose: STI clinic clients frequently receive antibiotics to treat sexually transmitted infections (STIs). This may select for antibiotic resistance among their commensal microbiota. We hypothesized that non-pathogenic oropharyngeal neisseriae of men who have sex with men (MSM) are less susceptible to antibiotics than those of the general population. Methods & Materials: In 2019-2020 we enrolled 96 participants at our STI clinic in Antwerp, Belgium: one group of 32 clinic employees representing the "general population" (group I) and two groups of 32 MSM (group II and III). Group I and II did not use antibiotics in the previous 6 months, whereas group III did. Eswabs TM were taken from their oropharynx, plated onto modified Thayer-Martin and blood agar and incubated in 5% carbon dioxide at 36.5°C for 24 hours. Neisseria -like colonies were identified to the species level with MALDI-TOF. Minimum inhibitory concentrations (MICs) of azithromycin, ciprofloxacin and ceftriaxone were determined by E-tests®. Species diversity and MICs were compared between groups using non-parametric tests. Results: Participants' median age was 35 (IQR 35 – 47.5). We isolated 172 non-pathogenic Neisseria colonies, representing seven different species. Data did not differ significantly between MSM of group II and III, so their data were combined. Prevalence of non-pathogenic neisseriae was 100.0% among employees and 51.6% among MSM ( p <0.0001). MICs of azithromycin and ciprofloxacin were significantly higher among MSM compared with employees (azithromycin: 8.0 mg/L [IQR 3.5–268.0 mg/L] versus 3.0 mg/L, [IQR 2.0–3.6 mg/L] p <0.001; ciprofloxacin: 0.250 mg/L [IQR 0.032–0.381 mg/L] versus 0.024 mg/L [IQR 0.016–0.101 mg/L], p <0.001). MIC of ceftriaxone did not differ significantly between MSM (0.056 [IQR 0.032–0.086 mg/L]) and employees (0.043 mg/L [IQR 0.028–0.056 mg/L], p =0.25). Conclusion: MICs of oropharyngeal neisseriae from members of the general Belgian population were remarkably high, and those from STI clinic clients were even higher. This probably results from repeated antibiotic exposure at the population level and warns us that novel resistance determinants may be readily available in these neisseriae for transfer to pathogenic neisseriae. This finding urges us to critically reconsider side-effects of current population-based interventions such as screening and treatment for asymptomatic STIs.